The Laissez-Faire Peasant: Post-socialist rural development in Serbia - Diković, Jovana (UCL Press, 2025)
In rural development studies there are two mainstream assumptions. One holds that peasants are the victims of state rural development schemes, the other that only planning can ensure change and prosperity in rural regions. It is rarely considered that peasants are architects of their own and local wellbeing – notions which are often in opposition to state plans for agriculture. The Laissez-Faire Peasant explores how rural development emerges on the ground. The concept involves the manifestation of peasant worldviews in which autonomy in decision-making, freedom of action, spontaneity, and flexibility in everyday cooperation play a dominant role. A role in which individual and local values generate a self-regulating system that manages a range of economic, social, and political relationships. The book examines manifestations of peasant autonomy, both in response to and independent of state rural development policies through a multi-sited ethnography of three Serbian villages. It is shown how these factors impede state programs for rural development while enabling the spontaneous flourishing of local communities. By focusing on the agency of rural residents, the book finds that peasants are resilient and competent agents who do not need government plans to thrive. Praise for The Laissez-Faire Peasant ‘Anthropologists and missionaries claim to love their peasants. Economists and planners claim to help them. Both look down. Diković brilliantly proposes a new approach, which might be called “humanomics’’. It gives respect, looking up from where people actually live.’ Deirdre Nansen McCloskey, University of Illinois at Chicago ‘This is an ethnographically rich and conceptually original study of post-socialist peasantry and rural development in Serbia. Jovana Diković draws a complex picture of the post-socialist peasants as autonomous and resilient subjects motivated by the visions of rural development anchored in their local lifeworlds.’ Agnieszka Joniak-Lüthi, University of Fribourg ‘In her excellent study Jovana Diković challanges the narrative about Serbian peasants usually viewed as downtrodden and exploited underdogs in need of governmental help. In this careful case study, these peasants represent an entrepreneurial, self -reliant and individualistic social group that can survive and thrive even in the conditions of modern and technologically advanced capitalism.’ Ivan Janković, Institut auf dem Rosenberg